2012
DOI: 10.1016/j.jsb.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and inhibition of the Plasmodium Atg8–Atg3 interaction

Abstract: The autophagy-related proteins are thought to serve multiple functions in Plasmodium and are considered essential to parasite survival and development. We have studied two key interacting proteins, Atg8 and Atg3, of the autophagy pathway in P. falciparum. These proteins are vital for the formation and elongation of the autophagosome and essential to the process of macroautophagy. Autophagy may be required for conversion of the sporozoite into erythrocytic-infective merozoites and may be crucial for other funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(101 citation statements)
references
References 66 publications
6
92
1
Order By: Relevance
“…13 All three compounds docked to the W-site of Pf Atg8 (Figure 3B). 2 and 3 bound with the pyridine ring in the W-site, whereas 1 was predicted to bind with the pyridine ring in the L-site, the thiazole ring positioned between the pockets, and the methylbenzene group in the W-site.…”
Section: Resultsmentioning
confidence: 99%
“…13 All three compounds docked to the W-site of Pf Atg8 (Figure 3B). 2 and 3 bound with the pyridine ring in the W-site, whereas 1 was predicted to bind with the pyridine ring in the L-site, the thiazole ring positioned between the pockets, and the methylbenzene group in the W-site.…”
Section: Resultsmentioning
confidence: 99%
“…31 While the surface-exposed residues located on one side of all Atg8 functional orthologs are highly conserved, many of the surface-exposed residues located on the opposite side of the protein exhibit low conservation, even among orthologs expressed in humans, which suggests that this side mediates interactions that are unique to different Atg8 orthologs. Plasmodium ATG8 orthologs share a unique inserted loop consisting of 9 amino acids between α-helix 3 and β-sheet 3, suggesting that such binding partners exist.…”
Section: Discussionmentioning
confidence: 99%
“…31 To provide further functional insights into the mechanism of this physical interaction, we next investigated this interaction using the yeast 2-hybrid system. The Gal4 BD-PbATG8 and Gal4 AD-PbATG3 fusion proteins were coexpressed in AH109 cells and grown on plates selective for interaction.…”
mentioning
confidence: 99%
“…It is reported that PfATG8 binds in vitro to a peptide of a PfATG3 homolog, indicating that an ATG8 conjugation pathway may exist in this parasite. 9 Association of PfATG8 with an autophagy-like process in Plasmodium has, however, not been described in detail. Moreover, it has been recently demonstrated that PfATG8 colocalizes with the apicoplast, a unique, non-digestive, chloroplast-like organelle that is essential to the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a mammalian ortholog of Atg8 known as LC3 interacts with cellular components such as microtubule-interacting proteins via their LC3-interacting domains or LIR domains 39 and it was previously shown that PfATG8 binds to the LIR domain of PfATG3, suggesting that the parasite protein contains structural features that allow protein-protein interactions that may mediate the transport of apicoplast-bound vesicles to their destination. 9 This parasitespecific role for PfATG8 may be explained by the presence of a Plasmodium-specific loop in PfATG8, 9 which could confer novel effector binding capacities that are absent in mammalian LC3 and yeast Atg8. Another atypical feature of PfATG8 is the lack of the C-terminal region beyond the glycine residue key for lipidation, and this characteristic could well have evolved to facilitate the second role of the protein in apicoplast formation and homeostasis.…”
mentioning
confidence: 99%